The Possible Encroachments on the People`s Power and the Fundamental Problems of their Regulation in the Law System of the Republic of Armeni - Vagharshyan, A. (Bulletin of Yerevan University C: Jurisprudence, 2019)
In the article the author offers a unique legal comment of the conctitutional resolution of “the appropriation of power” on the basis of the theoreticaldogmatic and comparative constitutional legal analysis and offers legal ways of improvement of RA criminal legislation in force.
Keywords: power, appropriation, usurpation, crime, violence, inviolability of essence, criminal law